Identificação de Mycobacterium bovis em leite através da reação em Cadeia da Polimerase - PCR - Marcos Santos Zanini (1998)
We developed a simple method for DNA extraction of Mycobacterium bovis in artificially infected milk to be used in diagnosis by the polymerase chain reaction (PCR). We compared the amplification pattem with set primers TBI-TB2 that yields a 383 bp fragment, set primers BW6-BW7 and BW8-BW9 that amplified a 306 bp and 248 bp, respectively. Set primers, BW6-BW7 and BW8-BW9 amplified iiagmerits present in six copies (IS1081) in strains of M bovis. Using this procedure, we detected until 102 CFU/ml or 5 pg of pure DNA. The method can be used for the routine diagnosis of Mycobacterium bavis in Milk samples.